2020
DOI: 10.1021/acs.jmedchem.0c01337
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tools for Illumination of Tuberculosis Biology, Virulence Mechanisms, and Diagnosis

Abstract: Tuberculosis (TB) remains one of the deadliest infectious diseases and begs the scientific community to up the ante for research and exploration of completely novel therapeutic avenues. Chemical biology-inspired design of tunable chemical tools has aided in clinical diagnosis, facilitated discovery of therapeutics, and begun to enable investigation of virulence mechanisms at the host−pathogen interface of Mycobacterium tuberculosis. This Perspective highlights chemical tools specific to mycobacterial proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 182 publications
(388 reference statements)
0
9
0
Order By: Relevance
“…Understanding lipid organization in the mycobacterial membrane may help guide the design of novel membrane-active antimicrobial drugs. Moreover, as many of the cell envelope lipids exert other important roles that contribute to the pathogenicity of Mtb , they have emerged as promising diagnostic biomarkers and therapeutic targets. , …”
Section: Complex Cell Membrane Envelope Of Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding lipid organization in the mycobacterial membrane may help guide the design of novel membrane-active antimicrobial drugs. Moreover, as many of the cell envelope lipids exert other important roles that contribute to the pathogenicity of Mtb , they have emerged as promising diagnostic biomarkers and therapeutic targets. , …”
Section: Complex Cell Membrane Envelope Of Mycobacteriamentioning
confidence: 99%
“…Moreover, as many of the cell envelope lipids exert other important roles that contribute to the pathogenicity of Mtb, they have emerged as promising diagnostic biomarkers and therapeutic targets. 71,72 The Mtb membrane envelope is organized into distinct compartments: the plasma or inner membrane, the peptidoglycan (PG)−arabinogalactan (AG) complex, the outer membrane (also referred to as mycomembrane), mycolic acids (MAs) covalently attached to the inner leaflet of the outer membrane, and free lipids noncovalently attached to the outer leaflet of the outer membrane (Figure 2). 73 This arrangement supports the structural, mechanical, metabolic, and osmotic functions of Mtb during different stages of infection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…An increasing number of published studies have reported on the staining of mycobacteria with labeled trehaloses, including 4-fluorescent-and 4-azido-trehaloses. [41][42][43][44][45][46][47] Mycobacteria have a thick cell wall with an outer membrane composed of several major lipids, including trehalose monomycolate (TMM) and trehalose dimycolate (TDM). TMM and TDM are synthesized in mycobacteria in processes involving multiple enzymes, transporters, and trehalose incorporation.…”
Section: Mycobacterium Staining With Imcta Probesmentioning
confidence: 99%
“…[48] Trehalose analogs, including fluorescently labeled ones, could be reportedly incorporated into TMM and TDM instead of trehalose. [41][42][43][44][45][46][47] Certain types of mycobacteriosis, such as that caused by multidrug-resistant tuberculosis and nontuberculous mycobacteria, are currently regarded as serious health problems worldwide. [49,50] The labeled trehalose probes could be new helpful tools to detect the pathogens of these mycobacterioses or investigate cell wall structures and functions as well as biosynthesis-related enzymes and transporters to develop new antibiotics and treatments.…”
Section: Mycobacterium Staining With Imcta Probesmentioning
confidence: 99%
See 1 more Smart Citation